Benzothiazolium-functionalized NU-1000: a versatile material for carbon dioxide adsorption and cyanide luminescence sensing. Issue 22 (8th May 2020) - Luconi, Lapo; Mercuri, Giorgio; Islamoglu, Timur; Fermi, Andrea; Bergamini, Giacomo; Giambastiani, Giuliano; Rossin, Andrea
Abstract : The benzothiazolium-decorated NU-1000-BzTz MOF is a versatile material for carbon dioxide storage and cyanide luminescence sensing in aqueous solutions. Abstract : A tailor-made benzothiazolium bromide salt functionality (BzTz ) is introduced via solvent-assisted ligand incorporation (SALI) into the mesoporous Zr-based metal–organic framework NU-1000 . The resulting NU-1000-BzTz composite has been thoroughly characterized in the solid state. The functional group loading has been determined through 1 H NMR analysis of the digested sample (5% HF-DMSO- d 6 ): a maximum value of 1.7 BzTz ligand per [Zr6 ] node is achieved. The material preserves its pristine crystallinity after SALI, as witnessed by powder X-ray diffraction. The functionalized MOF has a slightly lower thermal stability than its parent material ( T dec = 780 vs. 800 K, respectively). The N2 adsorption isotherm collected at 77 K disclosed that its BET specific surface area (1530 m 2 g −1 ) is lower than that of prisitine NU-1000 (2140 m 2 g −1 ), because of the space taken and weight added by the dangling benzothiazolium groups inside the pores. A total CO2 uptake of 2.0 mmol g −1 (8.7 wt% CO2 ) has been calculated from the CO2 adsoprtion isotherm collected at T = 298 K and p CO2 = 1 bar. Despite the lower BET area, NU-1000-BzTz shows an increased thermodynamic affinity for CO2 (isosteric heat of adsorption Q st = 25 kJ mol −1 ) if compared with NU-1000 ( Q st = 17 kJ mol −1 ), confirming that the presence of a polar functional group in the MOF pores improves the interaction with carbon dioxide. Finally, NU-1000-BzTz has been exploited as a luminescent sensor for polluting anions (CN −, SCN −, OCN −, and SeCN − as sodium or potassium salts) in aqueous solutions, after bromide exchange. A marked reversible blue shift of its emission band from 490 to 450 nm is observed in all cases, with the associated emission color change from light green to blue under a UV lamp. The detection limit of CN − (1.08 × 10 −6 M) is much lower than that measured for the other "stick-like" anions considered in this study. The process occurs efficiently even in the presence of other competing ions ( i.e. in ordinary tap water), opening promising application perspectives in cyanide luminescence sensing in drinking water.